(untitled) (Research, Society and Development, 2022)
Objective: To verify in the scientific literature the prevalence and factors related to musculoskeletal injuries in Jiu-Jitsu practitioners and describe which anatomical segments are most affected. Methodology: This is a systematic review, which took as reference the Preferred Reporting Items for Systematic Reviews and Meta-Analysis (PRISMA) protocol, in the Periodical Portals of the VHL (Virtual Health Library) and CAPES (Personnel Improvement Coordination). Higher Level). Observational epidemiological studies were included that evaluated the prevalence of orthopedic injuries in athletes practicing Jiu-Jitsu, from 2009 to 2020. Results: Four articles were selected from the 174 initially located, which presented as results the knee being the most anatomical segment stricken. In addition, males, beginner white and blue belt athletes, and those aged between 20 and 30 years were the most affected. However, regarding the time of practice, no prevalence of any period was observed. Conclusion: In this systematic review, it was observed that there is a high prevalence of musculoskeletal injuries in Jiu-Jitsu fighters. The most affected anatomical segment is the knee and the related factors vary according to certain variables, being more common in male athletes, beginners and young adults.